Intensity profile measurement for carbon steel pipe using gamma-ray tomography - Y.S., Susiapan; Abdul Rahim, Ruzairi; Goh, C.L.; F. R., Hafiz; A. R., Herlina (Penerbit UTHM, 2017)
This paper details a non-destructive type of tomographic technique to obtain the intensity profile of a carbon steel pipe. This method requires a radioactive source, where a detector-source pair is mounted on a circular gantry located around the periphery of a steel pipe. A radioactive source with an appropriate activity was chosen based on the thickness of the pipe under test. In order to detect gamma rays, photon scintillation detectors are required. A Thallium-activated Sodium Iodide (NaI(T1)) detector crystal was used. Stability tests were conducted on the detectors before they were ready to be used. A portable hardware to house the detector and source was then designed and built. For testing purposes, objects (polypropylene log, wax log, hollow polypropylene log, concrete log). The system was able to achieve an average accuracy of 96.283% when a comparison was done between actual dimension of the objects under test and the dimension based on the intensity profiles.